FEATURES OF BURNING DENTURES IN DIABETES MELLITUS - Atahanov Alisher Vohobjonovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In order for the provision of dental care to be high quality, it needs to be tailored to a variety of systemic and chronic diseases from which the patients suffer. This feature of dental care is due to the fact that different approaches and methods of providing such assistance contribute, first of all, to improve the health of patients, and improve their quality of life. The article describes the features of dental care for patients with chronic non-communicable diseases. According to the author, the Feedback of the dentist, endocrinologist, and therapist also plays an important role in improving the quality of care for patients with diabetes, as the dentist takes into account the recommendations of the endocrinologist (the use of certain drugs) and timely referral to the dentist of such patients by the therapist and endocrinologist will allow regular monitoring of the state of the teeth and oral cavity of patients. The author comes to the conclusion that patients suffering from diabetes mellitus are included in a special group of dental patients who should be under the special control of the dentist and receive his help in a timely manner to prevent the development of complications of the underlying disease and dental pathologies.